2004
DOI: 10.1177/147323000403200215
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Giant Aneurysms Complicating Arteriovenous Fistulae

Abstract: The creation of an arteriovenous fistula (AVF) is frequently used to achieve easier access for haemodialysis in patients with chronic renal insufficiency. The most frequent late complication of AVFs is aneurysm formation, which carries the risk of spontaneous rupture. This study reports on 18 patients with giant aneurysms that developed on antebrachial AVFs who were operated on over a period of 6 years. Colour duplex ultrasonographic examination of the upper extremity was performed in all but one patient in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 6 publications
0
30
0
4
Order By: Relevance
“…For localized aneurysms, resection with re-establishment of venous continuity has also been described. 11 This technique, however, is not applicable to the patient population described in this series.…”
Section: Discussionmentioning
confidence: 94%
“…For localized aneurysms, resection with re-establishment of venous continuity has also been described. 11 This technique, however, is not applicable to the patient population described in this series.…”
Section: Discussionmentioning
confidence: 94%
“…Surprisingly, there is no report in the literature on the effect of revision surgery in patients who present purely with complicated true or false AVA-related aneurysms. Only Karabay et al 42 have reported on purely surgical management of giant true aneurysms complicating antebrachial arteriovenous fistulas, but they did not mention the postintervention patency rates.…”
Section: Discussionmentioning
confidence: 97%
“…[13] The surgical treatment of choice can either be closure of the fistula with ligation or preserving the continuity of the fistula by partial resection of the aneurysm sac. [14,15] It is an effective method for the elimination of the aneurysm, and the risk of bleeding during surgery is less with this method than with other methods. However, it has a disadvantage in that the fistula cannot be used again.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Furthermore, early intervention was reported to be important since the risk of spontaneous rupture is a life-threatening complication. [15,18] In our cases, we operated on the aneurysm in the early period before the development of any complications. Therefore, we think that it is more efficient to do plication along with partial resection of aneurysm.…”
Section: Discussionmentioning
confidence: 99%